THE CHALLENGE OF TEACHING GENERATION Z - Cilliers, Elizelle Juaneé (PEOPLE: International Journal of Social Sciences, 2017)
Incredible technology changes are defining our current reality, impacting on our approach to society, to planning and to breaking new ground in terms of education. There is a rise of a new generation that is "location-aware" and speaks a “technological-language”. This has a great impacts on the teaching-learning environment within the current university structures, as students (the new Generation Z learners) are more equipped with technology, than typical Generation X (lecturers), which increase complexity of education processes involving instruction, guidance, and supervision. This study investigated the preferences of the new Generation Z student, in terms of technology usage within formal educational systems, based on the surveys conducted among the Urban Planning students on the Potchefstroom campus of the North-West University, South Africa, over a 7 year period. It also tested perspectives and technology usage and preferences of current lecturers (of the same group of students), in order to reveal some of the complex realities and challenges faced when teaching Generation Z. The research concluded with the viewpoints of both groups and presented some solutions to bridge the gaps and enhance teaching-learning strategies.